Dangerous masculinity: fatherhood, race, and security inside America's prisons - Curtis, Anna (Critical issues in crime and society, 2019)
Acknowledgements -- Introduction: masculinity, fatherhood, and race inside America's prisons -- Neoliberal responsibility and "being there" as a father -- Little me versus my princess : fathers' expectations about gender -- Unruly boys and dangerous men : security and masculinity in prison -- Game faces and going up the way : enacting masculinity in prison -- Conclusion: the conditions of possibility -- Appendix: Methods and research setting -- Works cited -- Index.